The evolution of the talent pathway in Major League Soccer - Mannix, P.; Roberts, S. J.; Enright, K.; Littlewood, M. (Soccer & Society, 2025)
Interest in North American soccer is re-emerging following the multiple announcements that major club (e.g., 2025 FIFA Club World Cup) and international tournaments (e.g 2026 FIFA World Cup) will be held on the continent in the coming years. However, there is a dearth of evidence on talent identification and development originating from this part of the world. The top-tier domestic league in the United States and Canada, Major League Soccer, operates as a single-entity business model and its clubs have gradually expanded their organizational structures, assembling youth academies and reserves teams, to help streamline a talent pathway into their first teams. The overall growth in Major League Soccer has ultimately created greater opportunities for homegrown domestic talents in North America, particularly the US. The present commentary highlights the evolution of the talent pathway within Major League Soccer, particularly during the better part of the previous two decades.